Criminal Liability Case Of Underage Motorcyclist Who Resulted In Death - Herson Tamutu (Estudiante Law Journal, 2019)
The purpose of this study is to find out how criminal liability in the accident of the passage of underage motorcyclists resulted in the death of the victim and know how the form of sanctions against minors who ride motorcycles resulted in the victim died in a traffic accident. This research uses normative research types or library research methods. Using several approaches, namely: the legal approach (statue approach), the case approach (case approach). First, the criminal liability of children in traffic accidents that result in the death of others is that the child can be criminally responsible for a separate process that is not the same as processing an adult. This is based on the provisions of Law No. 11 of 2012 in Article 2 in the implementation of the Criminal Justice System of Children is carried out based on the principle, protection, justice, non-discrimination, best interests for children, appreciation of opinions for children, survival and child development, development and guidance of propositional children, deprivation of independence and punishment as a last resort, and avoidance of retaliation. Second, that the form of punishment or sanctions and legal proceedings in cases of violations of the law by children is different from cases of violations of the law adults, in the investigation of cases of minors who commit criminal acts then investigators must apply restorative justice by seeking a diversion system processed by Law No. 11 of 2012 on the Child Justice System.Keywords: Accountability; minors; Laka lalu